Design, Development and Evaluation of Gliclazide Tablets for Non-Insulin Dependent Diabetes Mellitus - Dave, Vikas; Jain, Amit; Agarawal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2020)
The goal of the present work was to formulate the oral tablets of gliclazide for non-insulin dependent diabetes and provide a dosage form for prolonged period of time, in order to improve efficacy, reduce the frequency of total dose and better patient compliance. The powders were evaluated for angle of repose, bulk density, compressibility index and hausner’s ratio. All the tests revealed that powders showed excellent flow properties. The resulting tablets were evaluated for thickness, diameter, and uniformity of weight test, hardness, friability and drug content. In-vitro release of drug was performed using 7.4 pH phosphate buffers and dissolution was done. All the tablet formulations showed acceptable pharmacological properties and complied with pharmacopoeias standards.